Whole Blood for Civilian Urban Trauma Resuscitation: Historical, Present, and Future Considerations - Walsh, Mark; Fries, Dietmar; Moore, Ernest; Moore, Hunter; Thomas, Scott; Kwaan, Hau C.; Marsee, Mathew K.; Grisoli, Anne; McCauley, Ross; Vande Lune, Stefani; Chitta, Swetha; Vyakaranam, Sudhir; Waxman, Dan; McCurdy, Michael T.; Zimmer, Donald; Patel, Bhavesh; Thachil, Jecko (Seminars in Thrombosis and Hemostasis, 2020)
Whole blood (WB) has been used for more than a century for far-forward combat resuscitation. Following the Iraq/Afghanistan combat, maritime, and austere environment use of WB for the resuscitation of severely hemorrhaging patients, there has been an increasing use of WB for the civilian urban resuscitation environment population. The impetus for this was not just improved outcomes in far-forward hospitals, which had different populations and different needs than the civilian urban population, but also an application of the lessons suggested by recent 1:1:1 plasma:platelets:packed red cells fixed-ratio studies for patients with massive transfusion needs. Mechanistic, logistic, and standardization concerns have been addressed and are evolving as the WB project advances. A small number of studies have been published on WB in the civilian urban trauma population. In addition, European experience with viscoelastic testing and resuscitation with fibrinogen and prothrombin complex concentrate has provided another viewpoint regarding the choice of resuscitation strategies for severely bleeding trauma patients in urban civilian environments. There are randomized controlled trials in process, which are testing the hypothesis that WB may be beneficial for the civilian urban population. Whether WB will improve mortality significantly is now a matter of intense study, and this commentary reviews the history, mechanistic foundations, and logistical aspects for the use of WB in the civilian trauma population.
Keywords: whole blood; cold-stored whole blood; fixed ratios; fibrinogen concentrate therapy; prothrombin complex concentrate therapy; combat; civilian